Territories, Peoples, Sovereignty (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Nation States have three defining characteristics: government of a territory, rapport with a group of people and ownership of a sovereign power. All three of these characteristics are undergoing changes. Several developments involve a redefinition of the “State” and produce numerous contradictions, which can only be solved if we consider the historicity of both the phenomenal essence and the conceptual essence of the State. We need to rethink and reconceptualise the State within the context of the new tendencies and transformations delineated by globalisation.
Keywords: state; nation; globalisation; sovereignty; political rights